Bimetallic Flower-like NiCoP Encapsulated in an N-Doped Carbon Shell with Enhanced Lithium Storage Properties - Haoyu Tian; Lingyu Zhao; Linlin Wang; Zijie Xia; Wenqi Tan; Zheng Jiao (Batteries, 2023)
It continues to be a challenge to design innovative NiCoP composite anode materials to further improve rate capacity. In this work, bimetallic flower-like NiCoP encapsulated in an N-doped carbon shell (designated as NiCoP@NC) as a high-rate capable anode material for lithium-ion batteries (LIBs) was successfully designed and synthesized. The novel structure design combines the advantages of flower-like NiCoP (core) and N-doped carbon (shell). Flower-like NiCoP offers numerous interface and redox reaction sites for improving lithium storage, while the N-doped carbon shell effectively buffers volume expansion and enhances electrical conductivity. The synergistic effect between NiCoP and the N-doped carbon shell proposes a marvelous high-rate capacity (320 mA h/g even at 5 A/g) and a good cycle life with high reversible capacity (369.8 mA h/g for 700 cycles at 3 A/g with 81% retention). An investigation of kinetics performance shows that the introduction of the N-doped carbon shell enhances the charge transfer, and the pseudocapacitive behavior dominates the rapid Li+ storage of the NiCoP@NC electrode.